Construção da qualidade de gabiroba (Campomanesia pubescens) durante o desenvolvimento - Machado, Gilson Gustavo Lucinda (2022)
Campomanesia pubescens is a native species from Brazil that occurs in the Cerrado biome and produces fruits known as gabiroba. The objective of the present study was to evaluate the construction of the quality of gabiroba, through physical, chemical and physiological analyzes throughout its development. The experiment was carried out in a completely randomized design, with treatments consisting of fruit harvested at different stages of their development, from 9 to 63 days after anthesis, with harvest intervals of 9 days, in three replications. The fruit were analyzed for mass, diameter, relative growth rate, respiratory activity, color, total chlorophyll, total carotenoids, firmness, soluble and total pectin, pH, titratable acidity (AT), soluble solids (SS), total sugars, vitamin C, total phenolic (Folin- ciocalteau and FAST BLUE), antioxidant activity (β-Carotene/linoleic acid, FRAP and ABTS), proximate composition and mineral and phenolic profiles. The growth of gabiroba was marked by the synthesis of chlorophylls and carotenoids, while the ripening by the degradation of these compounds, with reflections on the color of the peel. The first 36 days of fruit development were marked by an increase in fruit firmness, while ripening by softening, accompanied by pectic solubilization. Reduction in AT throughout development was reflected in the increase in pH. The levels of SS and total sugars reduced from 9 to 27 days, increasing then until full ripening at 63 days. The concentration of vitamin C increased in the first days after anthesis followed by a fall that coincided with the ripening of the fruit. Total phenolic increased during the first 18 days of development, the phase with the highest growth rate, and then decreased. The fruits showed high antioxidant activity, with a tendency to decline during development. The development of gabiroba was marked by significant changes in the proximate composition. The mineral contents, analyzed individually, reduced linearly, along the fruit development. Nevertheless, the ingestion of 100 grams of ripe gabiroba can contribute with 4.47; 6.95; 3.20; 7.1; 1.54; 22.62; 9.56 and 11.11% of the recommended daily intake for Ca, Mg, P, K, Zn, Fe, Mn and Cu, respectively. Eleven phenolic compounds were identified in gabiroba, namely, in decreasing order of concentration: trigonelline, gallic acid, theobromine, vanillin and ferulic, m-coumaric, caffeic, syringic, p-coumaric, rosmarinic and trans-cinnamic acids. The use of Kohonen's self-organizing map corroborated the regression analyses, allowing to obtain complementary data regarding the grouping of fruits harvested at different stages, and to observe the similarities and correlation trends in a more effective and intuitive way.